9th International Munich Chassis Symposium 2018 chassis.tech plus - Pfeffer, Peter; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2019)
By forming the link between the road surface and the vehicle, the chassis plays a key role in enhancing vehicle dynamics and ride comfort. With its control systems, it provides the basis for the further development of driver assistance systems which support the driver in the task of driving the vehicle. This applies to an even greater extent to autonomous vehicles. Electromechanical steering and steer-by-wire systems are one solution available. At the same time, the brake system as a safety component needs to be developed in such a way that it fulfills the requirements of powertrain hybridization and electrification. Contents New chassis systems.- Autonomous vehicles.- Ride comfort.- Chassis control systems.- Development methods.- Elastomeric bearings and wheel suspension.- Innovative materials and methods.- Steering feel and human-machine interface (HMI).- New steering concepts.- Development methods.- Future brake systems.- Brake dust.- Brake control systems and vibration.- Wheel technologies and trends.- Tire testing and simulation.- Tire performance and tire slip analyses. Target audiences Automotive engineers and chassis specialists as well as students looking for state-of-the-art information regarding their field of activity - Lecturers and instructors at universities and universities of applied sciences with the main subject of automotive engineering - Experts, researchers and development engineers of the automotive and the supplying industry Publisher ATZ live stands for top quality and a high level of specialist information and is part of Springer Nature, one of the leading publishing groups worldwide for scientific, educational and specialist literature. Partner TÜV SÜD is an international leading technical service organisation catering to the industry, mobility and certification segment.
New chassis systems -- Autonomous vehicles -- Ride comfort -- Chassis control systems -- Development methods -- Elastomeric bearings and wheel suspension -- Innovative materials and methods -- Steering feel and human-machine interface (HMI) -- New steering concepts -- Development methods -- Future brake systems -- Brake dust -- Brake control systems and vibration -- Wheel technologies and trends -- Tire testing and simulation -- Tire performance and tire slip analyses.
Keywords: Automotive engineering; Engines; Automotive Engineering; Engine Technology